2018
DOI: 10.1038/s41467-018-07132-x
|View full text |Cite
|
Sign up to set email alerts
|

PRKAA1/AMPKα1-driven glycolysis in endothelial cells exposed to disturbed flow protects against atherosclerosis

Abstract: Increased aerobic glycolysis in endothelial cells of atheroprone areas of blood vessels has been hypothesized to drive increased inflammation and lesion burden but direct links remain to be established. Here we show that endothelial cells exposed to disturbed flow in vivo and in vitro exhibit increased levels of protein kinase AMP-activated (PRKA)/AMP-activated protein kinases (AMPKs). Selective deletion of endothelial Prkaa1, coding for protein kinase AMP-activated catalytic subunit alpha1, reduces glycolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 61 publications
2
81
0
Order By: Relevance
“…AMPK, a well-known energy sensor, could switch on glycolysis and induce autophagy to maintain ATP level 45 . It has been reported that AMPK could phosphorylate ULK1 to form PI3K complex, leading to autophagy induction 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…AMPK, a well-known energy sensor, could switch on glycolysis and induce autophagy to maintain ATP level 45 . It has been reported that AMPK could phosphorylate ULK1 to form PI3K complex, leading to autophagy induction 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the mRNA levels of Prkaa1 and Prkaa2 were much higher in leukocytes from adipose tissues of mice fed HFD for 8 weeks than mice fed chow diet (CD) ( Figure 1B ). Prkaa1 is the major isoform of Prkaa in leukocytes ( Zhang et al, 2017 ), and our recent study shows a critical role of Prkaa1 in metabolic regulation in vascular cells ( Yang et al, 2018 ). We analyzed expression of metabolic genes in sorted cells with qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…AMPK/PRKA also has been reported to regulate glycolytic flux through the pathway by phosphorylating phosphofructo-2-kinase/fructose 2,6-bisphosphatase 3 (PFKFB3), which affects the activity of PFK1, a rate-limiting enzyme in glycolysis ( Bando et al, 2005 ). Our previous study has demonstrated that AMPK/PRKA regulates glycolysis in part via the HIF1α pathway ( Yang et al, 2018 ), and increased HIF1A expression promotes glycolysis, resulting in a rapid supply of ATP ( Semenza, 2012 ). In addition to stimulating glycolysis, AMPK/PRKA also increases FAO by a reduction of the activity of ACC, decreased the level of malonyl-CoA, and resulted in increased fatty acid import into mitochondria for β-oxidation ( Saggerson, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK is a vital regulator of energy metabolism. In the prevention and treatment of AS, AMPK plays an important role in promoting cholesterol efflux, accelerating fatty acid oxidation and inhibiting inflammation [ 32 34 ]. Our results showed that colchicine treatment significantly increased the expression of phosphorylated AMPK and the downstream protein SIRT1.…”
Section: Discussionmentioning
confidence: 99%